STRATEGI KAMPANYE POLITIK PEMILIHAN KEPALA DESA DALAM UPAYA MENGGIRING OPINI PUBLIK : (Studi Pada PILKADES Serentak Kabupaten Blitar 2019) - Farkhan Evendi; Denny Arinanda Kurnia (Universitas Islam Balitar, 2020)
This research aims to find out how the strategy of political campaign was conducted in the selection of village heads to lead public opinion. This research is a descriptive study using a qualitative approach. The primary Data of the study is interview with informants and observations conducted by researchers. Secondary data is in the form of reports and official documents. The results showed that candidates could implement a good political campaign strategy. The advantage of the political product approach focuses on its products such as notes of the events which done in the past, and personality characteristics before the Pilkades in 2019 was held. The campaign strategy is a direct political marketing strategy to prospective voters and campaign strategies through the group. The strategy of direct political campaigns to prospective voters is done by face to face, and also conducting social activities, one of them is a healthy walking activity. While political marketing is done by through community leaders who are members of the volunteer team from each neighbourhood (RT).